1982
DOI: 10.1007/bf01370945
|View full text |Cite
|
Sign up to set email alerts
|

Ethologic analysis of the action of enkephalins on intraspecific behavior

Abstract: 612.821.i/.3.014.46:547.95:547.943 and M. I. Titov KEY WORDS: aggression; defense; intraspecific behavior; met-enkephalin; leu-enkephalin.The role of enkephalins and their analogs in the regulation of mechanisms of memory, analgesia, certain motor acts, and autonomic reactions has been demonstrated recently [4,[6][7][8]. However, the spectra of their action on intraspecific (zoosocial) behavior have not been analyzed.The aim of the present investigation was to analyze the spectrum of action of met-and leu-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
1982
1982

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…They are involved in memory mechanisms [Sandman and Kastin, 19771, analgesia [Kosterlitz and Hughes, 19751, and individual and social behavior [Poshivalov et al, 1982;Valdman et al, 19801. They can simultaneously function as neuromediators, neuromodulators, and neurohormones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are involved in memory mechanisms [Sandman and Kastin, 19771, analgesia [Kosterlitz and Hughes, 19751, and individual and social behavior [Poshivalov et al, 1982;Valdman et al, 19801. They can simultaneously function as neuromediators, neuromodulators, and neurohormones.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that endogenous neuropeptides and their synthetic analogs have a wide spectrum of neurotropic effects [De Wied, 1973;Kastin et al, 1979bl. They are involved in memory mechanisms [Sandman and Kastin, 19771, analgesia [Kosterlitz and Hughes, 19751, and individual and social behavior [Poshivalov et al, 1982;Valdman et al, 19801. They can simultaneously function as neuromediators, neuromodulators, and neurohor-mones.…”
Section: Introductionmentioning
confidence: 99%